Shafina Goes On A Goal - UPM striker helps team emerge champions - The Star, Ng Wei Loon (2008)
Hotshot striker Shafina Bazilah Shmasul was in top form to assist Universiti Putra Malaysia (UPM) to emerge as champions in the opening leg of the Malaysian Universities Sports Council (MASUM) Games Women's futsal competition at Universiti Malaya (UM) on Saturday.